The association of dietary patterns with incident chronic kidney disease and kidney function decline among middle-aged Korean adults: a cohort study - Jialei Fu; Sangah Shin (Epidemiology and Health, 2023)
OBJECTIVES This study assessed the association of dietary patterns with the incidence of chronic kidney disease (CKD) and kidney function decline among Korean adults. METHODS Data were collected from the records of 20,147 men and 39,857 women who participated in the Health Examinees study. Principal component analysis was used to identify 3 dietary patterns (prudent, flour-based food and meat, and white rice-based), and CKD risk was defined using the Epidemiology Collaboration equation for estimated glomerular filtration rate: (eGFR) <60 mL/min/1.73 m2. A kidney function decline was defined as a >25% decrease in eGFR from baseline. RESULTS During the 4.2-year follow-up, 978 participants developed CKD and 971 had a 25% decline in kidney function. After adjusting for potential impact variables, compared with the lowest quartile of the prudent dietary pattern, participants in the highest quartile had a 37% lower risk of kidney function decline among men (hazard ratio [HR], 0.63; 95% confidence interval [CI], 0.47 to 0.85); while higher adherence to the flour-based food and meat dietary pattern was associated with an increased risk of CKD in both men (HR, 1.63; 95% CI, 1.22 to 2.19) and women (HR, 1.47; 95% CI, 1.05 to 2.05) as well as a decline in kidney function in both men (HR, 1.49; 95% CI, 1.07 to 2.07) and women (HR, 1.77; 95% CI, 1.33 to 2.35). CONCLUSIONS Although a higher adherence to the prudent dietary pattern was inversely associated with the risk of kidney function decline in men, there was no association with CKD risk. In addition, a higher adherence to the flour-based food and meat dietary pattern increased the risk of CKD and kidney function decline. Further clinical trials are needed to confirm these associations.